Extraction and characterization of biological phytoconstituents of commiphora gileadensis leaves using soxhlet method - Aiman A., Mokaizh; Nour, Abdurahman Hamid; Alazaiza, M. Y. D.; Mustafa, Sara Elkheir; Omer, Manal Suliman; Nassani, Dia Eddin (MDPI, 2024)
Commiphora gileadensis is a medicinal plant with a wide range of biological characteristics. Many medical diseases can be treated using the leaves of C. gileadensis, including bacterial infections, inflammatory illnesses, and wounds. As a result, the Soxhlet extraction method was used to extract the phenolic components and measure the recovery yields from C. gileadensis leaf. The impacts of the Soxhlet extraction parameters (extraction time 30–150 min, sample/solvent ratio 1:20–1:40 g/mL, and concentration of ethanol solvent 20–100% v/v) on the total flavonoid content (TFC), total phenolic content (TPC), and extraction yield were investigated using the one-factor-at-a-time (OFAT) technique. Fourier transform infrared spectroscopy (FTIR) and gas chromatography–mass spectroscopy (GC–MS) analyses have been employed to evaluate the extracts for the presence of various phytochemicals. According to the results, the C. gileadensis leafs ethanolic extract extracted via the Soxhlet process achieved the maximum yields at 90 min of extraction time, a feed/solvent ratio of 1:30 g/mL, and a 40% v/v ethanol concentration. These yields were: extraction yield = 23.20 ± 0.10% w/w, TPC = 59.93 ± 1.33 mg GAE/g d.w., and TFC = 19.65 ± 1.77 mg QE/g d.w.. Further, a total of 20 phenolic components with excellent antioxidant characteristics were found in the leaf extract of C. gileadensis extracted via the Soxhlet method.